Electronic gambling machine gamblers' characteristics vary according to the type of gambling venue: a Canadian study. Issue 1 (2nd January 2016) - Sévigny, Serge; Leclerc, Martin; Goulet, Annie; Côté, Karina; Jacques, Christian; Ladouceur, Robert; Giroux, Isabelle
Abstract: The goal of this study was to improve the common knowledge on the connections between problem gambling and environmental settings. A cross-sectional design was used to compare two types of electronic gambling machine (EGM) users in terms of gamblers' self-reported behaviours, perceptions, motivations and preferences according to the type of venue they gambled in. Sixty-six volunteers who gambled in a gambling hall containing 335 EGMs were compared to volunteers ( n = 143) who gambled in small venues containing either 5 or 10 EGMs. All venues were located in areas with similar socio-economic status. Face-to-face survey-like interviews were conducted on site by trained assistants. Interviews comprised 83 items (fixed response and short open-ended questions). Gamblers' varied according to the type of venue on (a) socio-demographic variables; (b) correlates of gambling problems; (c) self-reported gambling behaviours, perceptions and motivations; and (d) venue characteristics influencing their choice of venue. Small venue gamblers reported more characteristics associated with problem gambling and are about four times more likely to be associated with problem gambling than gambling hall patrons. Decision-makers should consider the venue specific players' profiles outlined in this manuscript, and appreciate their possible use in appropriate responsible gambling measures and prevention/treatment programmes.